1976
DOI: 10.2307/2009974
|View full text |Cite
|
Sign up to set email alerts
|

State Power and the Structure of International Trade

Abstract: The structure of international trade, identified by the degree of openness for the movement of goods, can best be explained by a state-power theory of international political economy. This theory begins with the assumption that the nature of international economic movements is determined by states acting to maximize national goals. Four goals—aggregate national income, political power, social stability, and economic growth—can be systematically related to the degree of openness in the international trading sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
304
0
35

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 886 publications
(340 citation statements)
references
References 10 publications
1
304
0
35
Order By: Relevance
“…See also Marini (1972), Furtado (1973), andSunkel (1969). 10 The theory is reviewed in greater detail in Lake (1993). induce, or persuade other states into opening their markets to foreign trade and investment (Gilpin 1975(Gilpin , 1977Krasner 1976). Although plausible, these alternative intuitions did not produce a body of well-specified theory.…”
Section: Originsmentioning
confidence: 99%
“…See also Marini (1972), Furtado (1973), andSunkel (1969). 10 The theory is reviewed in greater detail in Lake (1993). induce, or persuade other states into opening their markets to foreign trade and investment (Gilpin 1975(Gilpin , 1977Krasner 1976). Although plausible, these alternative intuitions did not produce a body of well-specified theory.…”
Section: Originsmentioning
confidence: 99%
“…of the largest state in the system~for the entirety of this analysis, the United States! by global GDP in year t, using data compiled in the Penn World Table+ 64 This measure of hegemony, although somewhat crude, is closely related to that used in many previous studies+ 65 Earlier research has found that hegemony influences the formation of IOs as well as patterns of international conflict and cooperation; however, the strength of these relationships remains controversial+ 66 In addition to political factors, we analyze three key aspects of each state's economy+ Past research has linked economic wealth and size to both IO membership rates and democratic transitions, so it is important to control for these factors+ 67 Consequently, we include development, which is country i's per capita GDP in year t, and its gdp in t+ openness is country i's total foreign trade~imports plus Krasner 1976;Russett 1985;McKeown 1991;Busch 1995+ 66+ See Keohane 1984;Martin 1992;andMansfield 1994+ 67+ See Jacobson, Reisinger, andMathers 1986;Burkhart and Lewis-Beck 1994;Shanks, Jacobson, and Kaplan 1996+ exports! divided by its GDP in year t+ There is some evidence that increasing openness increases the propensity for states to join IOs+ 68 Furthermore, because the flow of overseas commerce is affected by the regime types of the trading partners, it is important to ensure that any relationship between democratization and IOs is not an outgrowth of international trade+ 69 We also include a trend~year!…”
Section: A Statistical Model Of Io Membershipmentioning
confidence: 99%
“…The stimulus was the apparent decline of American hegemony. Both Gilpin (1975b) and Krasner (1976), as well as the economist Charles Kindleberger (1973), were early exponents of the idea that global economic health was somehow dependent on the presence of a single dominant power -a view that Keohane (1980) later labeled the theory of hegemonic stability. Despite what seemed like an erosion of American power, however, the world economy did not appear rudderless.…”
Section: The Pioneersmentioning
confidence: 99%